The depressive symptoms of bulimia nervosa. - Cooper, P; Fairburn, C (1986)
Standardised measures of mental state were used to compare patients with bulimia nervosa with those with major depressive disorder. The two groups were found to be similar in terms of severity of psychiatric disturbance, as measured by the Montgomery and Asberg Scale and the Present State Examination. Noteworthy symptomatic differences were a greater frequency of obsessional ruminations and anxiety amongst the first group, and a greater frequency of depressed mood, apparent sadness, and suicidal ideation amongst the second. Discriminant function analyses revealed that the two patient groups had a different pattern of symptoms. Examination of the character of the psychiatric symptoms of patients with bulimia nervosa suggests that the anxiety and depressive symptoms are likely to be secondary to the eating disorder itself, rather than of primary significance.